Belief in a Just World Predicting Career Exploration through Future Time Perspective in Chinese Higher Education Students - Wei Li; Ching-Lin Wu (International Journal of Environment, Engineering and Education, 2026)
This study examined the relationship between belief in a just world, future time perspective, and career exploration among vocational college students in Guangxi, China. Drawing on Career Construction Theory, belief in a just world was conceptualized as an adaptive readiness factor, future time perspective as a cognitive-regulatory resource, and career exploration as an adapting response. A quantitative cross-sectional survey design was employed. Data were collected from 1,055 students enrolled in nine higher vocational institutions and analyzed using confirmatory factor analysis and structural equation modeling. The measurement model demonstrated satisfactory reliability, convergent validity, and discriminant validity. The structural model showed an acceptable fit to the data, with χ²/df = 2.43, RMSEA = 0.037, SRMR = 0.042, CFI = 0.96, and TLI = 0.95. The results indicated that belief in a just world was positively associated with career exploration and future time perspective. Future time perspective was also positively associated with career exploration and partially mediated the relationship between belief in a just world and career exploration. The model explained 30% of the variance in future time perspective and 46% of the variance in career exploration. These findings suggest that students’ fairness-related beliefs and future-oriented cognition are important psychological correlates of proactive career development behavior. The study extends Career Construction Theory by integrating just-world beliefs and future time perspective into a mediation framework for vocational students’ career exploration. Because the study used a cross-sectional design, the findings should be interpreted as theoretically grounded associations rather than causal evidence.